Positioning Biofortication and HarvestPlus at the National Level in Uganda - International Potato Center (2017)
Under the USAID-funded project, Meals for Nutrition: Biofortified Solutions (MENU), HarvestPlus has reached a total of 10,358 farmers (8,912 females and 1,446 males) with orange sweetpotato vines in 13 districts between October 2016 and September 2017, through six partner NGOS. The Uganda Multi-sectoral Food Security and Nutrition Project is scaling-up the production and utilization of biofortified vitamin A orange sweetpotato and high iron beans in another 15 districts through schools.